The Comprehension-Knowledge for Prospective Teachers as an Object of Educational Diagnostics - Blinstrubas, Artūras (Acta Paedagogica Vilnensia, 2002)
The paper reports part of the research, which aims at designing a theoretical basis for the Comprehension–Knowledge Test for Youth and Young Adults in Lithuania, corresponding to the social and cultural conditions of the country. A short theoretical analysis of the concept of comprehension-knowledge and its diagnostic sense is presented. The search for the sources of the test, task designing and selection process in one of the components of the test university student population are reviewed. The results of the test demonstrate diagnostic opportunities of the comprehension-knowledge of prospective teachers. Possibilities and prospects of predicting their success in university studies are being analysed. The most important result of the research is facts confirming the ability of the test to reveal individual differences in the comprehension-knowledge level of the subjects. The sense and practical importance of the diagnostics of the comprehension-knowledge construct are corroborated by the results of correlation research presented in this paper. An essential direct link (r = 0,55 and r = 0,51) has been established between the comprehension-knowledge test score and the evaluation of the university studies. On this basis the conclusion is formulated about the forecasting abilities of the designed „Comprehension-knowledge test for the Youth and Young Adults" in respect to the achievement in university studies. This fact is important for the practice of organization of higher education study process. The results of the research have also confirmed the suitability of the methodology used for the item selection. New hypotheses have been formulated about possibilities for further development and prospects of the diagnostic research presented in the paper.